Combined [18F]-FDG PET-MR imaging for monitoring small bowel crohn’s disease - Mattila, Juho; Kallio, Johanna; Löyttyniemi, Eliisa; Nuutila, Pirjo; Koffert, Jukka (Springer Nature, 2026)
Crohn’s disease (CD) is a chronic and relapsing inflammatory disease of the gastrointestinal tract. Diagnostics and follow-up are difficult in small bowel, that can be only partially evaluated by conventional endoscopy. Combined positron emission tomography magnetic resonance enterography (PET-MRE) has shown potential in diagnosing small bowel CD, but its role in monitoring treatment response has not been previously established. This study aimed to evaluate whether PET-MRE can be used to assess the efficacy of medical therapy. We hypothesized that standardized uptake values (SUV) in inflamed small bowel segments would decrease following initiation of standard therapy. A total of 35 volunteer patients with clinically suspected small bowel CD were recruited. All patients underwent ileocolonoscopy and laboratory testing, followed by [18F]-FDG PET-MRE. CD diagnosis was confirmed by small bowel capsule endoscopy. Clinicians initiated treatment based on standard diagnostics, blinded to the PET results. Eighteen patients completed follow-up [18F]-FDG PET-MRE at three months. Maximum SUV (SUVMax) was measured in the small intestine and compared with MRE findings. The median SUVMax decreased significantly from baseline to follow-up (3.2 vs. 2.1, p = 0.0025). The Simplified Magnetic Resonance Index of Activity (sMARIA) was also significantly lower at follow-up (p = 0.001). Representatively, median fecal calprotectin declined (451 µg/g vs. 163 µg/g, p = 0.004). This preliminary prospective study suggests that [18F]-FDG PET-MRE may be a useful tool for assessing biochemical response to treatment in newly diagnosed small bowel CD.